Refugee Policies and Narratives in the Globalised Era: The Case of Australia - Herrero, Dolores (International Journal of English Studies, 2021)
One of the effects of globalisation has been population mobility as a result of famine, climate warming and war conflicts, among other things. This flow of refugees, however, is often seen as a menace to the rule of law and human rights concomitant with the Western lifestyle. Refugees are no longer regarded as human beings and victims, but rather as danger, even as potential terrorists, which has led many governments, including the Australian, to detain them indefinitely in detention centres where they are confined in inhuman conditions. The main aim of this paper will be to describe Australian immigration policies and how contemporary Australian narratives on and by refugees are reflecting this situation, mainly by analysing a selection of texts from three recently published collections, namely, A Country Too Far (2013), They Cannot Take the Sky (2017) and Seabirds Crying in the Harbour Dark (2017), and Behrouz Boochani’s No Friend but the Mountains (2018).